Implant image quality in dental radiographs recorded using a customized imaging guide or a standard film holder - Schropp, Lars; Stavropoulos, Andreas; Spin-Neto, Rubens [UNESP]; Wenzel, Ann (Wiley-Blackwell, 2012)
Objective: To compare a customized imaging guide and a standard film holder for obtaining optimally projected intraoral radiographs of dental implants.Material and methods: Intraoral radiographs of four screw-type implants with different inclination placed in an upper or lower dental phantom model were recorded by 32 groups of examiners after a short instruction in the use of the RB-RB/LB-LB mnemonic rule. Half of the examiners recorded the images using a standard film holder and the other half used a customized imaging guide. Each radiograph was assessed under blinded conditions with regard to rendering of the implant threads and was assigned to one of four quality categories: (1) perfect, (2) not perfect, but clinically acceptable, (3) not acceptable, and (4) hopeless.Results: For the upper jaw, the same number of exposures per implant were made to achieve an acceptable image (P = 0.86) by the standard film holder method (median = 2) and the imaging guide method (median = 2). For the lower jaw, medians for the imaging guide method and the film holder method were 1 and 2, respectively (P = 0.004). For the imaging guide method, the first exposure was rated as perfect/acceptable in 62% of the cases and for the film holder method in 41% of the cases (P = 0.013). After <= 2 exposures, 78% (imaging guide method) and 69% (film holder method) of the implant images were perfect/acceptable (P=0.23). The implant inclination did not have a major influence on the outcomes.Conclusion: Perfect or acceptable images were achieved after two exposures with the same frequency either using a customized imaging guide method or a standard film holder method. However, the use of a customized imaging guide method was overall significantly superior to a standard film holder method in terms of obtaining perfect or acceptable images with only one exposure.
Keywords: dental; imaging guide; implant; intraoral; radiography